Use of Lung Ultrasound in Cystic Fibrosis: Is It a Valuable Tool? - Alessandra Boni; Luca Cristiani; Fabio Majo; Nicola Ullmann; Marianna Esposito; Maria Chiara Supino; Paolo Tomà; Alberto Villani; Anna Maria Musolino; Renato Cutrera (Children, 2024)
Cystic fibrosis (CF) is a multisystem disorder characterized by progressive respiratory deterioration, significantly impacting both quality of life and survival. Over the years, lung ultrasound (LUS) has emerged as a promising tool in pediatric respiratory due to its safety profile and ease at the bedside. In the era of highly effective CF modulator therapies and improved life expectancy, the use of non-ionizing radiation techniques could become an integral part of CF management, particularly in the pediatric population. The present review explores the potential role of LUS in CF management based on available data, analyzing all publications from January 2015 to January 2024, focusing on two key areas: LUS in CF pulmonary exacerbation and its utility in routine clinical management. Nonetheless, LUS exhibits a robust correlation with computed tomography (CT) scans and serves as an additional, user-friendly imaging modality in CF management, demonstrating high specificity and sensitivity in identification, especially in consolidations and atelectasis in the CF population. Due to its ability, LUS could be an instrument to monitor exacerbations with consolidations and to establish therapy duration and monitor atelectasis over time or their evolution after therapeutic bronchoalveolar lavage. On the basis of our analysis, sufficient data emerged showing a good correlation between LUS score and respiratory function tests. Good sensitivity and specificity of the methodology have been found in rare CF pulmonary complications such as effusion and pneumothorax. Regarding its use in follow-up management, the literature reports a moderate correlation between LUS scores and the type, extent, and CT severity score of bronchiectasis. A future validation of ultrasound scores specifically in CF patients could improve the use of LUS to identify pulmonary exacerbations and monitor disease progression. However, further research is needed to comprehensively establish the role of LUS in the CF population, particularly in elucidating its broader utility and long-term impact on patient care.